Pegylated interferon 2a and 2b in combination with ribavirin for the treatment of chronic hepatitis C in HIV infected patients - Ravinder Dhillon; Simona Rossi; Steven K Herrine (Dove Medical Press, 2008)
Ravinder Dhillon, Simona Rossi, Steven K HerrineDepartment of Medicine, Division of Gastroenterology and Hepatology, Thomas Jefferson University, Philadelphia, PA, USAAbstract: Coinfection with hepatitis C virus (HCV) and HIV is an increasingly recognized clinical dilemma, particularly since the advent of highly active antiretroviral therapy. Several studies of this population have demonstrated both more rapid progression of liver disease and poorer overall prognosis compared to HCV monoinfected patients. Consensus guidelines, based primarily on the results of 4 major randomized trials, recommend treatment with peginterferon and ribavirin for 48 weeks in coinfected patients. However, this current standard of care is associated with lower response rates to therapy than those seen in monoinfected patients. Important predictors of response include HCV genotype, pretreatment HCV RNA level, and presence of rapid virologic response (RVR) and early virologic response (EVR). Use of weight-based ribavirin dosing appears to be safe and enhances the likelihood of sustained virologic response (SVR). Adverse effects most commonly encountered are anemia and weight loss. Mitochondrial toxicity can occur in the setting of concomitant nucleoside reverse transcriptase inhibitor use, especially didanosine, abacavir, and zidovudine, and these should be discontinued before initiation of ribavirin therapy. Discontinuation of therapy should be considered in patients failing to demonstrate EVR, though ongoing trials are investigating a potential role for maintenance therapy in these patients. Peginterferon combined with weight-based ribavirin is appropriate and safe for treatment of HCV in HIV – HCV coinfected patients. This review summarizes the data supporting these recommendations.Keywords: hepatitis C, human immunodeficiency virus, peginterferon, ribavirin